The predictive value of NLR, SII, and complement 3 in treatment response for systemic lupus erythematosus with immune thrombocytopenia - Zheng, Ziqiang; Liu, Jiali; He, Taoyuan; Liu, Chang (Frontiers in Immunology, 2025)
ObjectiveTo evaluate the predictive value of systemic immune-inflammation index (SII), neutrophil-to-lymphocyte ratio (NLR), and complement 3 in the therapeutic outcomes of systemic lupus erythematosus-associated immune thrombocytopenia (SLE-ITP).MethodsClinical data from 72 patients diagnosed with SLE-ITP and admitted to the Affiliated Central Hospital of Dalian University of Technology between January 2013 and September 2024 were collected and analyzed. Associations between therapeutic outcomes and clinical characteristics, as well as laboratory findings including SII and NLR, were evaluated systematically.ResultsThe patients achieved complete remission (CR) 32 (44.4%), partial remission (PR) 19 (26.4%), and no remission (NR) 21 (29.2%). SII exhibited statistically significant differences among the three groups (P=0.027). The median SII values were 145.7 (43.7-238.7) for the CR group, 57.2 (20.5-90.2) for the PR group, and 117.8 (80.7-238.6) for the NR group. Additionally, complement 3 levels were significantly lower in the CR group compared to the PR and NR groups (P=0.010). Logistic regression analysis revealed that the NLR was positively correlated with therapeutic efficacy (OR=1.982, 95% CI: 1.18-3.33, P=0.010). SII and complement 3 were significantly negatively correlated with therapeutic outcomes (SII: OR=0.991, 95% CI: 0.984-0.998, P=0.011; C3: OR=0.045, 95% CI: 0.002-0.919, P=0.044). ROC curve analysis demonstrated that the combined predictive model of NLR, SII, and complement 3 achieved an area under the curve (AUC) of 0.743 (95% CI: 0.620-0.866, P=0.001), specificity of 76.2%, and sensitivity of 66.7%, indicating excellent predictive efficacy.ConclusionThe combined predictive model significantly enhances the predictive efficacy for SLE-ITP treatment outcomes compared to individual indicators.